2012
DOI: 10.1590/s1677-55382012000400010
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of percutaneous nephrolithotomy (PCNL): a prospective and randomized study comparing regional epidural anesthesia with general anesthesia

Abstract: Objective: To compare the efficacy and safety of regional epidural anesthesia and general anesthesia in patients who underwent PCNL. Materials and Methods: Fifty patients submitted to percutaneous nephrolithotomy (PCNL) were randomized into two groups: Group I (N = 26) received general anesthesia and Group II (N = 24) received regional epidural anesthesia. Demographic and operative data including age, BMI, stone position, stone size, postoperative pain, amount of postoperative analgesic usage, length of hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 10 publications
7
43
1
Order By: Relevance
“…11,18,25,26,28 Karacalar Serap et al studied 180 patients undergoing PCNL, concluded that CSE gave greater patient satisfaction, shorter times for PACU and home readiness, and less postoperative pain (p = 0.001). 20 Elbeally et al conducted a study on 57 patients undergoing PCNL in GA, epidural anaesthesia (EA) and paravertebral block (P).…”
Section: Postoperative Painmentioning
confidence: 99%
See 1 more Smart Citation
“…11,18,25,26,28 Karacalar Serap et al studied 180 patients undergoing PCNL, concluded that CSE gave greater patient satisfaction, shorter times for PACU and home readiness, and less postoperative pain (p = 0.001). 20 Elbeally et al conducted a study on 57 patients undergoing PCNL in GA, epidural anaesthesia (EA) and paravertebral block (P).…”
Section: Postoperative Painmentioning
confidence: 99%
“…Similar to our study Tangpaitoon et al, Karacalar Serap et al, Elbealy et al found increase in incidence of PONV in GA group as compared to CSE. 20,21,26 …”
Section: Ponvmentioning
confidence: 99%
“…The post operative pain as assessed by VAS showed that 34 patients had mild pain and 16 had moderate pain in Group 2(C), while most patients had no pain and only 13 patients had mild pain in Group 1(E) [Table 13a,13b,13c]. This difference in VAS is statistically significant and shows that effective analgesia is achieved with epidural Ropivacaine (11) . Other complications in recovery included shivering and hypertension which were more in Group (C).…”
Section: Discussionmentioning
confidence: 94%
“…It has vasoconstrictive properties at these concentrations which may explain its longer duration compared to Bupivacaine (7) . Sensory block with Ropivacaine is similar to Bupivacaine (8) but Ropivacaine showed greater separation of sensory and motor block (9), (10) and better patient satisfaction (11) . Studies have also showed that Ropivacaine is effective for intraoperative and postoperative analgesia in patients undergoing PCNL (12), (13), (14) .…”
Section: Introductionmentioning
confidence: 90%
“…They found the stone-free rate in the general anesthesia group was 71.37%, similar to the spinal anesthesia group 72.97% (p > 0.05) 35 . Kuzgunbay et al 36 and Tangpaitoon et al 37 also found that combined spinal-regional anesthesia is a feasible technique in PCNL operations because the efficacy and safety were not affected compared to PCNL with general anesthesia. Selection of anesthesia is important because it can affect the patient's postoperative recovery and a consideration for the urologist to discharge a patient from the hospital in a safe condition as soon as possible 38 .…”
Section: Discussionmentioning
confidence: 98%